Performing Paint, Claiming Space: The Santa Fe Indian School Posters on Paul Coze’s Stage in Paris, 1935 - Jessica L. Horton (Transatlantica)
This essay examines sixty-one extant posters that were hand-painted by students at the Studio School of the Santa Fe Indian School and sent to Paris to advertise an exhibition of their artwork, Art peau-rouge d’aujourd’hui (Redskin Art Today), at the Musée d’Ethnographie du Trocadéro in 1935. A collaboration between the students and Paul Coze, a French hobbyist and self-trained ethnographer, the commission was a dynamic component of a transatlantic assemblage that included Native objects and performers in Paris. Framed by printed French text, the figures that populated the posters engaged playfully with the city’s streets, museums, and stages, demonstrating the mutual porousness of graphic and performing arts. I show that although the students could not travel in the flesh, they claimed a space for Indigenous cultural values and experiences of modernity in the French capital.